1982
DOI: 10.4039/ent114431-5
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Studies of the Food Preferences of Some Orchard Carabids (Coleoptera: Carabidae)

Abstract: Can. Enr. 114: 431-437 (1982) Laboratory studies of the food preferences of several adult carabids showed that Amara aenea DeG., Anisodactylus sanctaecrucis F., Harpalus affinis Schr., and Stenolophus comma F. were polyphagous and readily fed on the seeds of several weeds as well as on young codling moth larvae and apple maggot pupae. H. affinis also attacked 4th and 5th instar codling moth larvae and pupae more readily than the other species. Pterostichus melanarius 111. showed a strong preference for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 8 publications
3
38
0
1
Order By: Relevance
“…The same was observed in laboratory experiments with A. parallelepipedus predating upon adults of D. reticulatum (Symondson, 1989), with H. rufipes predating on hatchlings of D. reticulatum (Ayre, 2001), or with C. nemoralis, P. melanarius and P. niger predating upon eggs and hatchlings of A. lusitanicus (Hatteland et al, 2010). Hagley et al (1982) also showed that P. melanarius kill prey even when satiated. Ayre (2001) attributed this wasteful or accidental killing to the way in which beetles assess potential prey, and pointed that such behaviour is a useful component in the impact that carabids may have on slug populations in the field.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The same was observed in laboratory experiments with A. parallelepipedus predating upon adults of D. reticulatum (Symondson, 1989), with H. rufipes predating on hatchlings of D. reticulatum (Ayre, 2001), or with C. nemoralis, P. melanarius and P. niger predating upon eggs and hatchlings of A. lusitanicus (Hatteland et al, 2010). Hagley et al (1982) also showed that P. melanarius kill prey even when satiated. Ayre (2001) attributed this wasteful or accidental killing to the way in which beetles assess potential prey, and pointed that such behaviour is a useful component in the impact that carabids may have on slug populations in the field.…”
Section: Discussionsupporting
confidence: 66%
“…Dempster (1967) found that predation on Pieris rapae (Linnaeus, 1758) by H. rufipes is most important during the smaller first two larval stages than in the third to fifth instars. Amara aenea (DeGeer, 1774) showed a strong feeding preference for small first instar larvae of Cydia pomonella (Linnaeus, 1758), being unable to subdue larger fourth instar larvae (Hagley et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In apple orchards, carabids are natural enemies of pests, preying on aphids (Hagley and Allen, 1990), apple maggot (Hagley et al, 1982), and potentially on other pests that have a life cycle stage in the soil, such as apple sawfly, apple twig cutter or apple leaf midge. Ground beetles have also been cited as preying on fifth-instar codling moth when the larvae seek a cocooning site on the ground (Glen and Milsom, 1978;Hagley et al, 1982;Hagley and Allen, 1988;Riddick and Mills, 1994), and some species could even feed on larvae in their cocooning shelters in the tree since they are able to climb plants in order to prey on pests (Dixon and McKinlay, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Ground beetles have also been cited as preying on fifth-instar codling moth when the larvae seek a cocooning site on the ground (Glen and Milsom, 1978;Hagley et al, 1982;Hagley and Allen, 1988;Riddick and Mills, 1994), and some species could even feed on larvae in their cocooning shelters in the tree since they are able to climb plants in order to prey on pests (Dixon and McKinlay, 1992). Although few studies have focused on the efficiency of carabid predation on codling moth, ground beetles seem to have only a slight effect in regulating this pest populations (Glen and Milsom, 1978;Hagley and Allen, 1988;Riddick and Mills, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…fat hen (Cbpodiium album) and ryegrass (Lolium sp.). Harpalus a&is is said to have similar habits in Britain (Alford 1984), but Hagley et al (1982) in a Canadian study found that under laboratory conditions H. a@nis was polyphagous, feeding on weed seeds and also young larvae of codling moth. In France, a study of the crop contents of H. a@nis taken in an apple orchard showed it to be generally phytophagous (fungal spores and pollen grains), but during July, 20-40% of the individuals examined had fed on larvae of Diptera and Lepidoptera (Comic 1973).…”
Section: Ecological Implicationsmentioning
confidence: 95%